2003
DOI: 10.1590/s0004-282x2003000200019
|View full text |Cite
|
Sign up to set email alerts
|

Myotonia congenita and myoadenylate deaminase deficiency: case report

Abstract: -Approximately 1-2% of the population has a deficiency of the enzyme myoadenylate deaminase. Early reports suggested that patients with myoadenylate deaminase deficiency had various forms of myalgia, and exercise intolerance. However, a deficiency of the enzyme has been described in many conditions, including myopathies, neuropathies, and motor neuron disease. We report a patient with clinical diagnosis of myotonia congenita and absent myoadenylate deaminase reaction on the muscle biopsy. This is the first des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…There are even reports of AMPD1-deficient patients presenting with postexertional myoglobinuria 124 and rhabdomyolysis. 125,126 MADA deficiency has been shown to coexist with other disorders of nerve and muscle such as myotonia congenita, 127 McArdle disease, 128 some of the muscular dystrophies, 129 and myasthenia gravis, 120 raising the possibility that primary and secondary forms of AMPD1 exists. However, a recent study has found no significant increase in the frequency of AMPD1 mutations in patients with neuromuscular disease compared with controls.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…There are even reports of AMPD1-deficient patients presenting with postexertional myoglobinuria 124 and rhabdomyolysis. 125,126 MADA deficiency has been shown to coexist with other disorders of nerve and muscle such as myotonia congenita, 127 McArdle disease, 128 some of the muscular dystrophies, 129 and myasthenia gravis, 120 raising the possibility that primary and secondary forms of AMPD1 exists. However, a recent study has found no significant increase in the frequency of AMPD1 mutations in patients with neuromuscular disease compared with controls.…”
Section: Clinical Featuresmentioning
confidence: 99%